Application of surfactants for the synthesis of qualitative hydroxide and metallic cobalt nanopowders - Nguyen, Van Minh; Nguyen, Tien Hiep; Gorobinsky, Stanislav V. (Journal of the Belarusian State University. Physics, 2021)
In this work, nanopowders (NP) Co(OH)2 were obtained by chemical precipitation from aqueous solutions of cobalt nitrate Co(NO3)2 and alkali NaOH (10 wt. %) using surfactants: sodium dodecyl sulfate (SDS) and cetylpyridinium chloride (CPC) (0.1 wt. %). It was shown that Co(OH)2 NP with 0.1% SDS is the best quality product, since its dispersion increases more than 2 times compared to the samples with 0.1% CPC and without surfactants. In this case, the Co(OH)2 NP has the form of flakes with an irregular shape and a nanometer size (about 100 nm) with an average thickness of 30 nm. It was found that the average particle size of Co NP obtained by hydrogen reduction of Co(OH)2 NP with 0.1% SDS at 280°C has a maximum on the distribution histogram shifted to the interval 41–50 nm, which is characterized by a narrow particle size distribution and represents spherical particles sintered with each other.